Socialism - Szalai Erzsebet (Central European University Press, 2005)
""In this book Prof Balcerowicz brings together 17 academic articles that summarise his research on the process of radical economic transformation... It is an impressive volume which makes a convincing case for the post-communist transition to be as rapid as possible."" - Financial Times Balcerowicz summarizes the research on institutions, institutional change, and human behavior that he has undertaken since the late 1970s, including the Polish model of economic reform.